Anti-obesity mechanism of Ganpu tea revealed by microbiome, metabolome and transcriptome analyses. (30th June 2023) - Liao, Yanfang; Wang, Chen; Gao, Zhipeng; Pan, Zhaoping; Peng, Mingfang; Ma, Jie; Qian, Yujiao; Guo, Jiajing; Fu, Fuhua
Highlights: Ganpu tea reduced inflammatory markers in high-fat-diet-induced obesity mice. The anti-obesity effect of Ganpu tea was related to the change in gut microbiota. Ganpu tea ameliorated metabolic disorders in high-fat-diet-induced obesity mice. Ganpu tea is a reliable strategy for preventing obesity in mice on a high-fat diet. Abstract: In this study, the anti-obesity mechanism of Ganpu tea (GPT) from the perspectives of microbiome, metabolome and transcriptome was investigated. GPT significantly reduced the high-fat-diet (HFD)-induced levels of inflammatory cytokines and the expansion of lipid droplets and white adipose tissue. GPT also improved HFD-induced gut microbiome imbalance by significantly reducing the proportion of Firmicutes to Bacteroidota . Metabolomic data showed that HFD-induced metabolic disorder was regulated by GPT and probably characterised by being related to 4-aminobutyraldehyde and 5-acetylamino-6-amino-3-methyluracil. Transcriptome showed that the improvement of obesity was mainly related to the IL-17 signaling pathway and the metabolism of xenobiotics by cytochrome P450. Spearman's correlation analysis indicated that gut microbiota were significantly correlated with inflammatory factors, genes and metabolites. Metabolome–transcriptome analysis showed that GPT reversed obesity mainly through the carbohydrate metabolism, amino acid metabolism and lipid metabolism. Collectively, GPT may be used as a health drink to prevent or treat obesity.